Biodistribution and Dosimetry Evaluation for a Novel Tau Tracer [18F]-S16 in Healthy Volunteers and Its Application in Assessment of Tau Pathology in Alzheimer’s Disease - Wang, Ying; Cai, Li; Zhou, Kaixiang; Cui, Mengchao; Yao, Shaobo (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The goal of this study was to report a fully automated radiosynthetic procedure of a novel tau tracer [18F]-S16 and its safety, biodistribution and dosimetry in healthy volunteers. And the potential utility of [18F]-S16 PET in AD. Methods: The automated radiosynthsis of [18F]-S16 was performed on a GE Tracerlab FX2 N module. For the biodistribution and dosimetry study, healthy volunteers were underwent a series PET scans acquired at 10, 60, 120 and 240min post-injection. The biodistribution and safety were assessed. For AD study, both AD and healthy controls (HCs) underwent dynamic [18F]-S16 and static [18F]-FDG PET imaging. [18F]-S16 binding was assessed quantitatively using SUV ratios (SUVRs) measured at different regions of interests (ROIs). [18F]-S16 SUVRs were compared between the AD and HCs using the Mann-Whitney U test. In AD patients with all cortical ROIs, Spearman rank correlation analysis was used to calculate the voxel-wise correlations between [18F]-S16 and [18F]-FDG. Results: The automated radiosynthesis of [18F]-S16 was finished within 45 min, with a radiochemical yield (RCY) of 30 ± 5% (n = 8, non-decay-corrected). The radiochemical purity (RCP) was greater than 98% and the specific activity (SA) was calculated to be 1047 ± 450 GBq/μmol (n = 5), and [18F]-S16 was stable in vitro. In healthy volunteer study, no adverse effect was observed within 24 hours post-injection and no defluorination was observed in vivo. The radiotracer could pass through the blood-brain barrier easily, and rapidly cleared from the circulation and excreted through the hepatic system. The whole-body mean effective dose was 15.3 ± 0.3 μSv/MBq. In AD, [18F]-S16 accumulation was identified involving parietal, temporal, precuneus, posterior cingulate and frontal lobes. No specific [18F]-S16 cerebral uptake was identified in HCs. SUVR of AD was significantly higher than that of HCs. No specific binding uptake was found in the choroid plexus, venous sinus and white matter. A significant correlation was found between [18F]-S16 binding and hypometabolism across neocortical regions. Conclusion: [18F]-S16 could be synthesized automatically and it showed favorable biodistribution and safety in human. [18F]-S16 PET indicated a high image quality for imaging tau deposition in AD, and distinguishing AD from HCs.